Global mRNA sequencing of human skeletal muscle: Search for novel exercise-regulated myokines - S. Pourteymour; K. Eckardt; T. Holen; T. Langleite; Sindre Lee; J. Jensen; K.I. Birkeland; C.A. Drevon; M. Hjorth (Elsevier, 2017)
Objective: Skeletal muscle is an important secretory organ, producing and releasing numerous myokines, which may be involved in mediating beneficial health effects of physical activity. More than 100 myokines have been identified by different proteomics approaches, but these techniques may not detect all myokines. We used mRNA sequencing as an untargeted approach to study gene expression of secreted proteins in skeletal muscle upon acute as well as long-term exercise. Methods: Twenty-six middle-aged, sedentary men underwent combined endurance and strength training for 12 weeks. Skeletal muscle biopsies from m. vastus lateralis and blood samples were taken before and after an acute bicycle test, performed at baseline as well as after 12 weeks of training intervention. We identified transcripts encoding secretory proteins that were changed more than 1.5-fold in muscle after exercise. Secretory proteins were defined based on either curated UniProt annotations or predictions made by multiple bioinformatics methods. Results: This approach led to the identification of 161 candidate secretory transcripts that were up-regulated after acute exercise and 99 that where increased after 12 weeks exercise training. Furthermore, 92 secretory transcripts were decreased after acute and/or long-term physical activity. From these responsive transcripts, we selected 17 candidate myokines sensitive to short- and/or long-term exercise that have not been described as myokines before. The expression of these transcripts was confirmed in primary human skeletal muscle cells during in vitro differentiation and electrical pulse stimulation (EPS). One of the candidates we identified was macrophage colony-stimulating factor-1 (CSF1), which influences macrophage homeostasis. CSF1 mRNA increased in skeletal muscle after acute and long-term exercise, which was accompanied by a rise in circulating CSF1 protein. In cultured muscle cells, EPS promoted a significant increase in the expression and secretion of CSF1. Conclusion: We identified 17 new, exercise-responsive transcripts encoding secretory proteins. We further identified CSF1 as a novel myokine, which is secreted from cultured muscle cells and up-regulated in muscle and plasma after acute exercise. Keywords: Exercise, Myokine, Colony stimulating factor 1, RNA sequencing, Skeletal muscle secretome